Ameliorative effect of quercetin against arsenic-induced sperm DNA damage and daily sperm production in adult male rats. (2nd July 2016) - Jahan, Sarwat; Rehman, Saima; Ullah, Hizb; Munawar, Asma; Ain, Qurat Ul; Iqbal, Tariq
Abstract: In this study, the protective effect of quercetin was evaluated against arsenic induced reproductive ailments in male rats. For this purpose, male rats ( n  = 5/group) weighing 180–250 g were used. First group served as control, second group received arsenic (50 ppm) in drinking water. Third group was treated with quercetin (50 mg/kg) alone, while fourth group received arsenic + quercetin. All treatments were carried out for 49 days. After treatment, animals were killed by decapitation; testis and epididymis were dissected out. Right epididymis was minced immediately for comet assay, while left epididymis was processed for histology. Similarly, right testis was homogenized for estimation of daily sperm production (DSP) and detection of metal concentration. The results of our research revealed that arsenic treatment did not cause any significant change in body weight and testicular volume. Quercetin treatment significantly prevented tissue deposition of arsenic within the testis. Arsenic treatment caused a significant reduction in DSP, however, in the arsenic + quercetin-treated group and quercetin alone-treated group, DSP was significantly high as compared to the arsenic-treated group. Histological study of epididymis showed empty lumen in arsenic-treated group while in arsenic + quercetin-treated group and quercetin alone-treated group, lumen were filled with sperm and were comparable to control. Sperm DNA damage, induced by arsenic, was significantly reversed toward control levels by supplementation of quercetin. These results suggest that quercetin not only prevents deposition of arsenic in tissues, but can also protect the sperm DNA damage.